2005
DOI: 10.1159/000088950
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Drugs for Chemotherapy of Bladder Tumours

Abstract: Background: Bladder cancers have different angiogenic pathways distinguishing not only papillary from solid tumours, but even papillary superficial from papillary invasive ones, thus representing selective targets for antiangiogenic drugs. Methods: The bacterial wall component tecogalan, inhibiting basic fibroblast growth factor (bFGF), the fumagillin derivative TNP-470, inhibiting vascular endothelial growth factor (VEGF), the distamycin A derivative PNU153429, and the tetracycline minocycline were administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…An understanding of the cellular and molecular basis of tumor angiogenesis, and a means of measuring its extent, are therefore important for clinicians who diagnose and treat cancer by whatever modalities. We would like to direct the readers to an excellent review of antiangiogenic drugs for chemotherapeutic treatment of bladder tumors which has been published in Chemotherapy [150] .…”
Section: Glut1 As a Marker Of Hypoxiamentioning
confidence: 99%
“…An understanding of the cellular and molecular basis of tumor angiogenesis, and a means of measuring its extent, are therefore important for clinicians who diagnose and treat cancer by whatever modalities. We would like to direct the readers to an excellent review of antiangiogenic drugs for chemotherapeutic treatment of bladder tumors which has been published in Chemotherapy [150] .…”
Section: Glut1 As a Marker Of Hypoxiamentioning
confidence: 99%
“…showed that anti-VEGF drugs have a potential benefit in bladder tumors that express VEGF. [27] However, anti-VEGF drugs in bladder tumor therapy are considered investigational yet.…”
Section: Discussionmentioning
confidence: 99%
“…ABT-510 is a peptide mimetic of thrombospondin-1, designed for blocking angiogenesis [29,30]. Dalteparin targets heparin associated modulation of angiogenesis [31][32][33]. Previously we have described series of flavonoids as potential anti-angiogenic, anti-cancer and antioxidant agents.…”
Section: Introductionmentioning
confidence: 99%